Corrosion Inhibition Effects of Some New Synthesized N-Aroyl-N-Aryl thiourea Derivatives for Carbon Steel in Sulfuric Acid Media - Al-Jeilawi, Uday H R; Al-Majidi, Suaad M H; Al-Saadie, Khulood A S (Al-Nahrain Journal of Science, 2018)
This research includes the synthesis of some new N-Aroyl-N-Aryl thiourea derivatives namely: N-benzoyl-N-(p-aminophenyl) thiourea (STU1), N-benzoyl-N-(thiazole) thiourea (STU2), N-acetyl-N`-(dibenzyl) thiourea (STU3). The series substituted thiourea derivatives were prepared from reaction of acids with thionyl chloride then treating the resulted with potassium thiocyanate to affored the corresponding N-Aroyl isothiocyanates which direct reaction with primary and secondary aryl amines, The purity of the synthesized compounds were checked by measuring the melting point and Thin Layer Chromatography (TLC) and their structure, were identified by spectral methods [FTIR,1H-NMR and 13C-NMR].These compounds were investigated as a corrosion inhibitor for carbon steel in 1M H2SO4 solution using weight loss, potentiostatic polarization methods; the obtained results showed that the substituted thioureas retard both cathodic and anodic reactions in acid media, by virtue of adsorption on the carbon steel surface. This adsorption obeyed Langmuir’s adsorption isotherm. The inhibition efficiency of (STU1-3) is ranging between (60-95)%. By using different (STU3) derivative concentration and temperature, the carbon steel corrosion rate was decreased with increasing (STU3) concentration and the highest inhibition efficiency reach to 98.5% by using 5×10-4 M (STU3) concentration at 338 K, the inhibition efficiency increases with increasing temperature in the range of (308-338)K.